CRITERIA INDICATORS OF THE LEVEL OF FORMED CREATIVE SKILLS OF EDUCATIONAL CHARACTER IN STUDENTS - M. Baditsa (Academy of Cognitive and Natural Sciences, 2010)
The article describes the separate aspects of complex study of the formed level of creative abilities of graphic for students, characterizes territorial indexes.